2014
DOI: 10.1016/j.icarus.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a large-scale flux rope and current sheet region on the dayside of Mars: MGS MAG/ER and MEX ASPERA-3 ELS observations

Abstract: a b s t r a c tWe present dual spacecraft observations by MGS MAG/ER and MEX ASPERA-3 ELS of a large-scale magnetic flux rope on the dayside of Mars that occurs in close proximity to the crustal magnetic fields and a dayside current sheet region. A current sheet (including the large-scale flux rope) was observed on repeated MGS orbits when the draped solar wind magnetic field present in the ionosphere had a þB y component (in MSO). Minimum Variance Analysis (MVA) of the large-scale flux rope and two current sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The actual spatial difference between these commensurable orbits is smaller than ∼300 km. Analogous investigations were performed solely for the MGS measurements by Soobiah et al [].…”
Section: Identification Of Martian Ionospheric Flux Ropesmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual spatial difference between these commensurable orbits is smaller than ∼300 km. Analogous investigations were performed solely for the MGS measurements by Soobiah et al [].…”
Section: Identification Of Martian Ionospheric Flux Ropesmentioning
confidence: 99%
“…orbits is smaller than ∼300 km. Analogous investigations were performed solely for the MGS measurements by Soobiah et al [2014]. Figure 1 shows an overview of the MAVEN magnetic field measurements when the spacecraft is at altitudes lower than 1000 km on orbit #1094.…”
Section: Identification Of Martian Ionospheric Flux Ropesmentioning
confidence: 99%
“…These studies suggest that there are unstudied physical processes producing isotropic and trapped distributions on closed crustal field lines, as conservation of adiabatic invariants and collisional scattering predicts a source cone distribution. More recently, Soobiah et al () observed field‐aligned low‐energy electrons and trapped high‐energy electrons inside of an ionospheric flux rope and, during times of radial field lines, with low‐energy PADs that indicate they are open. The electron impact ionization cross sections for the primary upper atmosphere neutral species, CO 2 and O, peak around 100 eV (Itikawa, ; Thompson et al, ).…”
Section: Introduction/motivationmentioning
confidence: 99%
“…Injection and trapping of electrons on closed magnetic field lines have been observed near the Martian crustal magnetic fields [ Brain et al , ; Ulusşen and Linscott , ; Harada et al , ; Xu et al , ]. Magnetic flux ropes can be formed by reconnection between draped interplanetary fields in the induced tail current sheets, between crustal and draped fields, or between neighboring crustal fields [ Brain et al , ; Briggs et al , ; Beharrell and Wild , ; Eastwood et al , ; Hara et al , , ; Soobiah et al , ; DiBraccio et al , ]. In order to evaluate the role of reconnection in their generation processes, it is necessary to characterize the basic properties of magnetic reconnection at Mars based on in situ observations of particle and field signatures around X lines.…”
Section: Introductionmentioning
confidence: 99%